Aplikasi Metode Microwave Hydrodistillation pada Ekstraksi Minyak Atsiri dari Bunga Kamboja (Plumeria alba) - Nove Kartika Erliyanti; Erwan Adi Saputro; Rachmad Ramadhan Yogaswara; Elsa Rosyidah (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2020)
The aim of this study is to determine the effect of microwave power and solvent volume to the density of Frangipani essential oil, and to determine the yield effect of mass of raw material on Frangipani essential oil. Frangipani flowers that have been cut in the size of ± 2 cm are extracted in the microwave with a mass of 25 gr and 50 gr, volume of solvents is 300, 400, 500, and 600 ml. The extraction process uses microwave power of 300, 450, and 600 watt and the extraction time is three hours. The results showed that the effect of microwave power and the volume of solvent had a significant effect on the density of Frangipani flower essential oils. The result showed that the density is increase when the microwave power and the volume of solvent increase. The highest density is produced at 600-watt microwave power, 600 ml solvent volume, and 50 gram of Frangipani flower mass that is equal to 0.904 gram/ml. Yield decreases with increasing mass of raw material used. The highest yield was produced at 600-watt microwave power, 600 ml solvent volume, and 25-gram Frangipani mass, which is equal to 1.612%.C